Urban planning today : a Harvard design magazine reader - Saunders, William S. (Harvard design magazine readers, 2006)
Urban Planning Today reports on projects in Atlanta, Boston, Chicago, New York, and Portland, bringing perspectives of urban design, city planning, criticism, and law to bear on the mixed bag of results observed in these cities.